Experimental Test Evaporator Cooling Machine Adsorption Cycle Solar with Collector Area 1 M2 Slope 30o Using Activated Carbon-Methanol As Adsorbent-Adsorbate Pair - Parna Edy Sitanggang (International Journal of Mechanical Computational and Manufacturing Research, 2022)
The need for cooling systems for a variety of needs perceived life is increasing, while the existing cooling system is very wasteful in the use of electricity and also lack of environmental friendly. Therefore, in this study have a cooling system using a pair of adsorption by activated carbon and methanol material - the material is easily available and do not produce pollution, resulting in cooling systems that are environmentally friendly. One part of the refrigeration cycle is a solar adsorption with type Evaporator Finned evaporator (Finned Evaporator). The research at to look at the rate of heat transfer in the evaporator and the heat absorbed by the evaporator of the cooling medium. The result showed a minimum temperature of water at 10 ° C, total rate of transfer of heat from the water to refrigerant during the adsorption cycle of 9.